Analisis Sistem Informasi Akuntansi Kas untuk Meningkatkan Efektivitas Pengendalian Internal pada Perumda Air Minum Wair Pu’an - Da Rato, Yessi; D. D. Kolit , Yuliana Anggreani; Noeng , Amanda Yecci (Universitas Nusa Nipa Maumere, 2026)
This study aimed to evaluate the implementation of the accounting information system for cash receipts and disbursements in supporting the effectiveness of internal control, with reference to the COSO framework components at the Regional Public Company Water Supply Wair Pu’an. The data used in this research included primary and secondary data. A qualitative descriptive method was employed, which describes or depicts the research objects based on observable facts. Dara collection methods included documentation and interviews with relevant stakeholders. The findings indicate that, overall, the accounting information system for cash receipts and disbursements at Perumda Water Supply Wair Pu’an is functioning effectively, as evidenced by the alignment of its internal control system with the COSO components.